Augmenting tomato functional genomics with a genome-wide induced genetic variation resource - Gupta, Prateek; Dholaniya, Pankaj Singh; Princy, Kunnappady; Madhavan, Athira Sethu; Sreelakshmi, Yellamaraju; Sharma, Rameshwar (Frontiers in Plant Science, 2024)
The induced mutations accelerate crop improvement by providing novel disease resistance and yield alleles. However, the alleles with no perceptible phenotype but having an altered function remain hidden in mutagenized plants. The whole-genome sequencing (WGS) of mutagenized individuals uncovers the complete spectrum of mutations in the genome. A genome-wide induced mutation resources can improve the targeted breeding of tomato and facilitate functional genomics.In this study, we sequenced 132 doubly ethyl methanesulfonate (EMS)-mutagenized lines of tomato and detected ca. 41 million novel mutations and 5.5 million short-INDELs not present in the parental cultivar. About 97% of the genome had mutations, including the genes, promoters, UTRs, and introns. More than 1/3 rd of genes in the mutagenized population had one or more deleterious mutations predicted by SIFT. Nearly 1/4 th of deleterious genes mapped on tomato metabolic pathways modulating multiple pathway steps. In addition to the reported GC>AT transition bias for EMS, our population also had a substantial number of AT>GC transitions.Comparing mutation frequency among synonymous codons revealed that the most preferred codon is least mutagenic towards EMS. The validation of a potato leaf-like mutation, reduction in carotenoids in ζ-carotene isomerase mutant fruits, and chloroplasts relocation loss in phototropin1 mutant validated the mutation discovery pipeline. Our database makes a large repertoire of mutations accessible to functional genomics studies and breeding of tomato.